A Systematic Comparison Identifies an ATP-Based Viability Assay as Most Suitable Read-Out for Drug Screening in Glioma Stem-Like Cells - A. Kleijn; J. J. Kloezeman; R. K. Balvers; M. van der Kaaij; C. M. F. Dirven; S. Leenstra; M. L. M. Lamfers (Stem Cells International)
Serum-free culture methods for patient-derived primary glioma cultures, selecting for glioma stem-like cells (GSCs), are becoming the gold standard in neurooncology research. These GSCs can be implemented in drug screens to detect patient-specific responses, potentially bridging the translational gap to personalized medicine. Since numerous compounds are available, a rapid and reliable readout for drug efficacies is required. This can be done using approaches that measure viability, confluency, cytotoxicity, or apoptosis. To determine which assay is best suitable for drug screening, 10 different assays were systematically tested on established glioma cell lines and validated on a panel of GSCs. General applicability was assessed using distinct treatment modalities, being temozolomide, radiation, rapamycin, and the oncolytic adenovirus Delta24-RGD. The apoptosis and cytotoxicity assays did not unequivocally detect responses and were excluded from further testing. The NADH- and ATP-based viability assays revealed comparable readout for all treatments; however, the latter had smaller standard deviations and direct readout. Importantly, drugs that interfere with cell metabolism require alternative techniques such as confluency monitoring to accurately measure treatment effects. Taken together, our data suggest that the combination of ATP luminescence assays with confluency monitoring provides the most specific and reproducible readout for drug screening on primary GSCs.